Link between ghost artefacts, source suppression and incomplete calibration sky models - Nunhokee, Chuneeta Devi (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2015)
Calibration is a fundamental step towards producing radio interferometric images. However, naive calibration produces calibration artefacts, in the guise of spurious emission, buried in the thermal noise. This work investigates these calibration artefacts, henceforth referred to as "ghosts" . A 21 cm observation with the Westerbork Synthesis Radio Telescope yielded similar ghost sources, and it was anticipated that they were due to calibrating with incomplete sky models. An analytical ghost distribution of a two-source scenario is derived to substantiate this theory and to seek answers to the related bewildering features (regular ghost pattern, points spread function-like sidelobes, independent of model flux). The theoretically predicted ghost distribution qualitatively matches with the observational ones and shows high dependence on the array geometry. The theory draws the conclusion that both the ghost phenomenon and suppression of the unmodelled flux have the same root cause. In addition, the suppression of the unmodelled flux is studied as functions of unmodelled flux, differential gain solution interval and the number of sources subjected to direction-dependent gains. These studies summarise that the suppression rate is constant irrespective of the degree of incompleteness of the calibration sky model. In the presence of a direction-dependent effect, the suppression drastically increases; however, this increase can be compensated for by using longer solution intervals.
Keywords: Interferometry; Calibration